Pengaruh Ekologi Dan Lingkungan Terhadap Ekowisata Mangrove Di Pantai Mangrove Paluh Getah, Desa Tanjung Rejo Kec. Percut Sei Tuan, Kab. Deli Serdang - Nazwa Aulia Azhari; Mita Nalsalisa Br Barus; Arma Fauziah; Meilinda Suriani Harefa; Syukri Hidayat (STIPAS Tahasak Danum Pambelum Keuskupan Palangkaraya, 2023)
Botanical gardens and zoos are living collection areas designed to preserve living plant and animal species. Biodiversity throughout the Indonesian archipelago represents the country's potential, and each region of the Indonesian archipelago has its own unique species of flora and fauna. Therefore, in addition to establishing protected areas as a conservation measure, rare animals and nature tourism from each region are also identified. Cocoons and national animals characterize and identify each region. National animals with puspa. Used as a mascot or regional identity.